Doing Participatory Action Research: Reflections on Criticality and Social Justice from the Researchers’ Perspective - Kemp, Linda; Bailey, Di; Barnard, Adam (Participatory Social Work: Research, Practice, Education, 2019)
This chapter explores Participatory Action Research (PAR) from the perspective of researchers who have applied PAR practises in two projects in the United Kingdom which are offered here as case studies. The first case study is a PAR based project which contemplates PAR by utilising the concept of “talking” as an activity for co-constructing knowledge about how young people who self-harm could be better helped when visiting their General Practitioners (GPs). The second is a Knowledge Transfer Partnership (KTP), funded to improve a UK local authority’s children’s service and participation of children and young people in service design and delivery. Each case study is written and reflected upon by an individual contributor to this chapter. The chapter outlines what participatory action research is and advocates why PAR is valuable for Social Work. Case studies are then introduced and critically discussed leading to the authors’ critical self-reflections and concluding comments.